THE THE EFFECT OF MANJUJAI-BASED PSYCHOSOCIAL STIMULATION EDUCATION USING ANIMATED VIDEO ON THE KNOWLEDGE AND ATTITUDE OF MOTHERS WITH CHILDREN AGED 6–24 MONTHS : PSYCHOSOCIAL STIMULATION EDUCATION - Perdana, Shintia; Helmizar, Helmizar; Azrimaidaliza, Azrimaidaliza (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: According to the Indonesian Ministry of Health's 2016 Health Profile, 56.4% of children under five years old experience growth and development disorders. This study aims to determine the effect of Manjujai-based psychosocial stimulation education using animated video on the knowledge and attitude of mothers with children aged 6–24 months. Methods: This study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. A total of 60 respondents were selected using purposive sampling. The study was conducted from April to May 2025. Data were analyzed up to the multivariate level using the General Linear Model (GLM). Results: The independent t-test showed a significant difference (p < 0.001) in the mean score changes of maternal knowledge and attitude between the intervention and control groups. This indicates that Manjujai-based psychosocial stimulation education through animated video has a significant effect on improving maternal knowledge and attitude. Multivariate analysis using GLM confirmed the significant effect of the intervention (p < 0.001) after controlling for confounding variables. Conclusion: Psychosocial stimulation education using animated video is proven to significantly improve maternal knowledge and attitude in providing psychosocial stimulation care for children.